USING PROGRESSIVE PEDAGOGIES TO ENHANCE LEARNER AUTONOMY - Miller, Lindsay (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
In this presentation I firstly review different approaches and methods that have been used toteaching English. Based on these approaches and methods, our understanding of how studentslearn their second language has been greatly enhanced. However, students in the 21st Centuryhave more demands and needs than previously and we now have to use more progressivepedagogies to teach them. Some features of a progressive pedagogical approach are: learnersare active participants; teachers are facilitators and guides; there is shared decision-making bythe group; learning is seen as part of real-life experiences; and learning is conceptualized as aspiral where knowledge is constructed through experience and social interaction (Peters, 2012).This type of pedagogical approach is student-centred and lends itself to the promotion of learnerautonomy. By way of an example I will talk about a university level English for Science course Ihave been involved in developing and teaching over the past five years.Keywords: Progressive pedagogies, learner autonomy, project learning.